Investigation of the Mighty Servant 3 accident by a progressive flooding method - Dankowski, Hendrik; Dilger, Hendrik (Volume 1: Offshore Technology, 2013)
The semi-submersible heavy-lift vessel MIGHTY SERVANT 3 sank off the port of Luanda, Angola in the morning of December 6th, 2006 during a ballast operation to offload the drilling platform Aleutian Key. The official investigations carried out after the accident identified an error in the control of the submerging ballast operations as the direct cause of the sinking. However, the detailed phenomenons and reasons for the sudden excessive trim development has not been investigated further. This paper intends to identify the most likely sceneario which lead to the hydrostatic stability failure during the discharge operation by computing the flooding process during the ballast operation in the time domain. A numerical progressive flooding simulation method is presented for applications like accident investigations or damage stability assessments. This method is modified to fit the special requirements of simulating the operational procedures of semi-submersible vessels in the time domain. Extensions like the inclusion of pump elements but also the multi-body interaction of the cargo and the vessel with regard to the hydrostatics is presented. The direct flooding simulation computes the flux between the compartments based on the Bernoulli equation and the current pressure heads at each intermediate step. Large and partly flooded holes are taken into account as well as optional air compression and flooding through completely filled rooms. Pressure losses due to viscous effects are taken into account by applying semi-empirical discharge coefficients to each opening. The flooding paths are modeled by directed graphs. A detailed investigation of the MIGHTY SERVANT 3 accident and an identification of the possible failure modes leading to the sinking of the vessel is presented. This will help to better understand the phenomenons leading to critical situations during the submerging procedure of semi-submersible heavy-lift vessels and to avoid such accidents in the future. Applying time domain flooding simulations allows to ...